Plant communities of Namibe saltmarshes (Southwest of Angola) - Cardoso, João Francisco (2021)
This work constitutes the first phytosociological analysis of saltmarshes on the Angolan coast. Sixty-five relevés were carried out resulting in the description of six new plant associations. These saltmarshes are characterized by a lower floristic richness when compared to the Holarctic saltmarshes. Eighteen taxa were identified, some of them succulent. Saltmarshes occur from the mouth of the Cunene River to the Cuanza River, although in this last part they are already very impoverished. In the Cuanza river, saltmarshes occupy only a narrow strip in the inner sector of the mangroves in contact with continental ecosystems and are often made up of just one taxon, Sarcocornia natalensis subsp. affinis. Mangroves reach their southern limit in the city of Lobito, although they are almost extinct there. The occurrence and distribution of saltmarshes are affected by the Cold Benguela Current, that influences the west coast of Africa between Cabo da Boa Esperança and Benguela. The height of the saltmarsh’s platforms colonized by halophyte, sub-halophyte or halotolerant plants determines the flooding period and thus the plant community’s floristic composition. Soil granulometry also plays an important role in the spatial organization of plant communities. One of the main originalities of Angolan saltmarshes is the predominance of fine sandy or sandy-loam soil texture as a consequence of the proximity of the Namibe desert. The PCA segregated the different plant communities described